On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Multi-objective optimization of glutathione production by Saccharomyces cerevisiae in a mini-bubble column reactor via a multifactorial batch-design approach - Isabella Giraldo-Rodriguez; Ángela M. Ossorio-Tróchez; Isabella M. Giraldo-Castro; Carlos A. Diaz; Andres Ceballos-Bermudez; Carlos A. Alvarez-Vasco; Colomba M. Dazzarola; José R. Perez-Correa; Nelson H. Caicedo-Ortega (Bioresource Technology Reports, 2025)

Gene dysregulation impairs placental angiogenesis in allogeneic pig pregnancies - Cristina A. Martinez-Serrano; Josep M. Cambra; Manuel Alvarez-Rodriguez; Inmaculada Parrilla; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez (Animal Reproduction Science, 2025)

Root nodulation and growth in nursery garden of Neltuma flexuosa var. depressa (Fabaceae), a framework species for Monte Desert ecological restoration - F.N. Zorbalas; A. Alvarez; D.R. Pérez; M.E. Rodriguez Araujo; T.A. Valfré Giorello; L.J. Lagos (Journal of Arid Environments, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Environmental fluoxetine promotes skin cell proliferation and wound healing - Quentin Rodriguez-Barucg; Angel A. Garcia; Belen Garcia-Merino; Tomilayo Akinmola; Temisanren Okotie-Eboh; Thomas Francis; Eugenio Bringas; Inmaculada Ortiz; Mark A. Wade; Adam Dowle; Domino A. Joyce; Matthew J. Hardman; et al. (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Reproductive physiology of the boar: What defines the potential fertility of an ejaculate? - Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano; Manuel Alvarez-Rodriguez; Emilio A. Martinez; Jordi Roca (Animal Reproduction Science, 2024)

Cooling rate modifies the location of aquaporin 3 in spermatozoa of sheep and goat - Belén Pequeño; María Gemma Millán de la Blanca; Cristina Castaño; Adolfo Toledano-Díaz; Milagros Cristina Esteso; Esther Alba; Francisco A. Arrebola; Rodolfo Ungerfeld; Belén Martínez-Madrid; Manuel Alvarez-Rodriguez; Heriberto Rodriguez-Martinez; Julián Santiago-Moreno (Theriogenology, 2024)

Spatially heterogeneous discharge of glacial meltwater to drainages surrounding the ablating Coropuna ice cap, Peruvian Andes - Elizabeth J. Olson; Lisa R. Welp; Marty D. Frisbee; Sebastián A. Zúñiga Medina; Odiney Alvarez-Campos; Wendy R. Roque Quispe; Carol I. Salazar Mamani; Midhuar R. Arenas Carrión; José Diaz Rodriguez; Juan Manuel Jara Gonzalez; Alexander Ccanccapa-Cartagena; Chad T. Jafvert (Hydrological Sciences Journal, 2024)

Pharmacokinetics and safety of LEAD-452, an EGFR-specific 4-1BB-agonistic trimerbody in non-human primates - Rocío Navarro; Susana Frago; Oana Hangiu; Ainhoa Erce-Llamazares; Rodrigo Lázaro-Gorines; Miguel A. Morcillo; José L. Rodriguez-Peralto; Laura Sanz; Marta Compte; Luis Alvarez-Vallina (Toxicology and Applied Pharmacology, 2024)

Unveiling Sticholysin II and plasmid DNA interaction: Implications for developing non-viral vectors - Felipe A. Escalona-Rodriguez; Yoelys Cruz-Leal; Javier La O-Bonet; Julio A. Pérez-Erviti; Mario Ernesto Valdés-Tresanco; Ada L. Rivero-Hernández; Maricary Sifontes-Niebla; Alexis Manso-Vargas; Belinda Sánchez; Carlos Alvarez; Leandro R.S. Barbosa; Rosangela Itri; et al. (Toxicon, 2024)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Bovine embryos release extracellular vesicles with differential miRNA signature during the compaction and blastulation stages - Bárbara Melo-Báez; Edwin A. Mellisho; Yat S. Wong; Joel Cabezas; Diego Caamaño; Constanza Aguilera; Gonzalo Riadi; Fidel O. Castro; Lleretny Rodriguez-Alvarez (Reproductive Biology, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Development of a Co2+/PMS process involving target contaminant degradation and PMS decomposition - O. M. Rodriguez-Narvaez; M. O. A. Pacheco-Alvarez; K. Wróbel; J. Páramo-Vargas; E. R. Bandala; E. Brillas; J. M. Peralta-Hernandez (International Journal of Environmental Science and Technology, 2020)

Adaptation of a Methanogenic Consortium to Arsenite Inhibition - Lucia Rodriguez-Freire; Sarah E. Moore; Reyes Sierra-Alvarez; James A. Field (Water, Air, & Soil Pollution, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

Dengue virus type 2 in Cuba, 1997: conservation of E gene sequence in isolates obtained at different times during the epidemic - R. Rodriguez-Roche; M. Alvarez; T. Gritsun; D. Rosario; S. Halstead; G. Kouri; E. A. Gould; M. G. Guzman (Archives of Virology, 2005)